Enhanced tribological properties of filled modified polytetrafluoroethylene with flower-shaped MoS2/C - Aoyu ZHAO; Wenzheng DONG; Yanxiang CHEN; Rong YANG; Qiquan LIN (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2025)
In order to enhance the inadequate wear resistance of polytetrafluoroethylene (PTFE) without compromising its advantage of low friction coefficient, the MoS2/C-PTFE composites were prepared. The flower-shaped and layer MoS2/C were synthesized via the hydrothermal reaction and mechanical agitation, respectively. Thermal stability, tribological properties and wear mechanism of composites at different carbon content were comprehensively investigated. It was demonstrated that the optimal carbon content for layered MoS2/C filled PTFE is 1%, while the optimal carbon content of flower-shaped MoS2/C filled PTFE is 1.5%. Deviating from these optimal levels, either with excessively high or excessively low carbon contents, can detrimentally affect the tribological properties of the composites. The results show that PTFE composites filled with flower-shaped MoS2/C exhibit superior friction stability and wear resistance compared to those filled with layered MoS2/C, both at room temperature and high temperatures. At room temperature, the main wear mechanism of the PTFE composites filled with flower-shaped MoS2/C is that of slight abrasive wear. At high temperatures, the wear mechanism for pure PTFE is mainly abrasive wear, transitioning to adhesive wear as the temperature increases. Upon introducing modified powder into the sample, the main wear mechanism shifts to abrasive wear. This can be attributed to the enhanced ability of PTFE composites filled with flower-shaped MoS2/C to form a uniform and continuous transfer film between themselves and the counter material during friction tests.